2022
DOI: 10.1038/s41467-022-31790-7
|View full text |Cite
|
Sign up to set email alerts
|

Heparin induces α-synuclein to form new fibril polymorphs with attenuated neuropathology

Abstract: Abstractα-Synuclein (α-syn), as a primary pathogenic protein in Parkinson’s disease (PD) and other synucleinopathies, exhibits a high potential to form polymorphic fibrils. Chemical ligands have been found to involve in the assembly of α-syn fibrils in patients’ brains. However, how ligands influence the fibril polymorphism remains vague. Here, we report the near-atomic structures of α-syn fibrils in complex with heparin, a representative glycosaminoglycan (GAG), determined by cryo-electron microscopy (cryo-EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…47 Heparin has been found to induce α-synuclein to form new fibril polymorphs with diminished neuropathology. 48 In a previous study, by using all-atom molecular dynamics (MD) simulations, we found that O-GlcNAcylation suppressed the oligomerization of α-synuclein via a steric effect, in which the additional O-linked glycosyl group decreased hydrogen bonds between α-synuclein monomers. 49 Knowledge of that mechanism illuminates recent experiments showing that proper O-GlcNAcylation can prevent the aggregation and fibrosis of α-synuclein, 41,43,50,51 as well as sheds light on the steric effect on protein aggregation.…”
Section: ■ Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…47 Heparin has been found to induce α-synuclein to form new fibril polymorphs with diminished neuropathology. 48 In a previous study, by using all-atom molecular dynamics (MD) simulations, we found that O-GlcNAcylation suppressed the oligomerization of α-synuclein via a steric effect, in which the additional O-linked glycosyl group decreased hydrogen bonds between α-synuclein monomers. 49 Knowledge of that mechanism illuminates recent experiments showing that proper O-GlcNAcylation can prevent the aggregation and fibrosis of α-synuclein, 41,43,50,51 as well as sheds light on the steric effect on protein aggregation.…”
Section: ■ Introductionmentioning
confidence: 94%
“…For example, fibrils purified from patients with multiple system atrophy are believed to be modified via covalent PTMs as well as noncovalent binding with unidentified molecular ligands . Heparin has been found to induce α-synuclein to form new fibril polymorphs with diminished neuropathology …”
Section: Introductionmentioning
confidence: 99%
“…Heparin, a heparan sulfate analog, has been shown to promote the fibrillation of α-syn. 235 In a recent structural study, it was found that heparin binds directly to several positively charged lysine residues (Lys32, Lys34, Lys43, Lys45, Lys58, Lys60, and Lys97) 236 and aligns on the positive surface along the fibril axis, resulting in intensive electrostatic interaction with the stacking lysine residues (Fig. 7a(i), top).…”
Section: Atomic View Of the Amyloid Fibril And Its Dynamic Regulationmentioning
confidence: 99%
“…Different Asyn fibril polymorphs are produced by incubating human recombinant monomeric Asyn protein under different conditions to induce fibril formation, including differences in pH, buffers and salts, as demonstrated by SSNMR [14][15][16][17][18][19][20][21] and cryo-EM studies [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] . The structure of Asyn fibrils isolated from postmortem multiple system atrophy (MSA) brain tissue, where fibrils accumulate in oligodendroglial cells, has been determined by cryo-EM 37 .…”
Section: Mainmentioning
confidence: 99%